تدریس مقرر الخدمات المکتبیة للتعلیم الالکترونى لطلاب أقسام المکتبات والمعلومات العربیة :دراسة تخطیطیة - د. أمانى زکریا Zakari; د.غدیر مجدى (المجلة الدولية لعلوم المكتبات والمعلومات)
With the growing popularity of e-learning worldwide, the role of thelibrary in supporting this type of learning has become indisputable; anddespite the implementation of several e-learning projects in various Arabuniversities; and the emergence of two Arab periodicals interested inpublishing research supporting e-learning, Arab library & information sciencestudents have not been adequately prepared yet to provide the appropriateservices to both, the Faculty working with the e-learning system ,and theirstudents. To solve this problem, this study was prepared ,aiming to featurethe importance of the role of library specialist in supporting and developing elearning, and also to mention the most important library services needed tosupport e-learning faculty and students , in addition to the technologies,programs ,and tools needed to support them. the study also aimed atexploring the opportunities available for , and the challenges facing theteaching of " library services for e-learning" curriculum, at the LISdepartments in the Arab world.Finally, the study ended with the design of the mentioned curriculum ,that can be taught in the Arab LIS departments ,in order to qualify students toprovide e-learning support services after they graduate.